1990
DOI: 10.1161/01.cir.82.1.147
|View full text |Cite
|
Sign up to set email alerts
|

Attenuated forearm vasodilative response to intra-arterial atrial natriuretic peptide in patients with heart failure.

Abstract: It has been shown that renal responses to atrial natriuretic peptide (ANP) are markedly attenuated in patients with heart failure. This study aimed to determine if vasodilative response to ANP is altered in patients with heart failure. In patients with heart failure (n=7) and age-matched normal subjects (n=7), forearm blood flow was measured using a strain-gauge plethysmograph during intra-arterial infusion of a.human ANP (50, 100, 200, and 400 ng/min) or nitroglycerin (100, 200, 400, and 600 ng/min). Forearm … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
34
1

Year Published

1994
1994
2009
2009

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(38 citation statements)
references
References 45 publications
3
34
1
Order By: Relevance
“…116 However, the cardiovascular and cGMP responses to exogenous ANP or BNP are markedly attenuated, indicating a downregulation or impaired receptor or postreceptor responsiveness of GC-A (as demonstrated by Hirooka et al 117 and many others). Some studies have suggested that the decreased biological responses to ANP are partly due to an upregulation of NPR-C receptors in peripheral tissues, leading to increased sequestration and degradation of ANP.…”
Section: Relevance Of Alterations In the Anp/gc-a System To Cardiovasmentioning
confidence: 89%
“…116 However, the cardiovascular and cGMP responses to exogenous ANP or BNP are markedly attenuated, indicating a downregulation or impaired receptor or postreceptor responsiveness of GC-A (as demonstrated by Hirooka et al 117 and many others). Some studies have suggested that the decreased biological responses to ANP are partly due to an upregulation of NPR-C receptors in peripheral tissues, leading to increased sequestration and degradation of ANP.…”
Section: Relevance Of Alterations In the Anp/gc-a System To Cardiovasmentioning
confidence: 89%
“…Many studies have detailed the central hemodynamic, arterial, renal, and adrenal effects of exogenous [1][2][3][4][5][6][7][8] and endogenous 9 NPs in animal models of HF 1 and in human HF, 2-9 but little is known about the effects of NPs on the capacitance vasculature in this condition. In the present study, we assessed the effects of all 4 currently known human NPs on the forearm vasculature in matched groups of optimally treated cHF patients.…”
Section: Discussionmentioning
confidence: 99%
“…[2][3][4][5][6][7] Hirooka et al 4 and Nakamura et al 6,17 reported reduced forearm resistance-vessel responses to intra-arterial infusion of ANP and BNP (but not CNP) in HF patients versus healthy controls. Interestingly, in these studies, changes in FBF to BNP and CNP were less than those in ANP (on an equimolar basis) in healthy controls, but approximately equipotent in patients with HF.…”
Section: Mechanism Of the Attenuated Forearm Resistance-vessel Responmentioning
confidence: 99%
See 1 more Smart Citation
“…39 This suggests that NPR-A may be important in the regulation of vascular smooth muscle tone in a range of vessels. Interestingly, in patients with HF, the efficacy of both endogenous and exogenously infused natriuretic peptide induced vasodilatation is significantly reduced 9,40 when compared with healthy volunteers. In our study, we report that the density of NPR-A in coronary artery is significantly downregulated in IHD patients compared with histologically normal coronary artery.…”
Section: Downregulation Of [ 125 I]-dnp Binding Density In Heart Failurementioning
confidence: 99%